ANALISIS PENGARUH KEPUASAN, TRANSPARANSI DAN AKUNTABILITAS TERHADAP LOYALITAS MEMBAYAR INFAQ DAN SEDEKAH (Studi Pada Lembaga Pengelola Zakat “PAY&DoIT” Kota Jakarta) - Nugraha, Alvin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The potential for ziswaf in Indonesia continues to increase every year, but the amount of ziswaf collected is insignificant compared to the potential for ziswaf which reaches 327.6 trillion rupiahs. As non-profit organizations, zakat management institutions need to pay attention to several variables so that donors are willing to spend part of their wealth, and this will create donor loyalty. This study uses satisfaction, transparency, and accountability variables to determine whether these variables affect donor loyalty. In this study, data were collected through questionnaires with purposive sampling. Respondents in this study amounted to 50 respondents who donated their wealth through the zakat management institution